Prevalence of self-reported sensitivities to various environmental factors in Germany, Sweden, and Finland based on multiple classification criteria - Köteles, Ferenc; Witthöft, Michael; Bräscher, Anne-Kathrin; Bailer, Josef; Nordin, Steven (Journal of psychosomatic research, 2026)
Objective - Our knowledge on the prevalence of self-reported sensitivities to environmental factors is poor. The lack of accepted criteria/assessment makes findings of different studies difficult to compare; the way of assessment might play a role in the reported prevalence rates. The present study aimed to report the prevalence rates of five environmental sensitivities for the German general population, to compare three of them with Swedish and Finnish data, and to demonstrate the impact of strictness of criterion on the results. - Methods - Data from a German (n = 2515), a Swedish (n = 3253) and a Finnish (n = 1467) population-based survey was used. Sentitivities were rated on ordinal scales in all samples. - Results - In the German sample, about 25 % of participants reported mild reactions to sounds, chemicals, and buildings, and about 10 % to electromagnetic fields (EMFs) and wind turbines, with a similar pattern for strong reactions, but with proportions of 1-2 %. Data from the Nordic countries show consistent similarities between these two countries, with prevalences exceeding 34 % for mild reactions to chemicals and sounds and about 5 % to EMFs, with a similar pattern for strong reactions, but with proportions of 1-8 %. Prevalence of sensitivity to EMFs was higher, whereas prevalence of sensitivity to chemicals and sounds was lower in Germany. Classification criteria significantly impacted the reported prevalence rates. - Conclusion - Various environmental sensitivities affect a considerable proportion of the general populations of the three countries. To improve comparability, self-report assessment of sensitivities should be based on at least an ordinal scale instead of the widely used yes-or-no question.